2010
DOI: 10.1080/00150193.2010.482886
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition Near the Morphotropic Phase Boundary in Pb(Zn1/3Nb2/3)O3- PbTiO3

Abstract: A new phase diagram in the poled sample of PZN-PT was proposed in a wider temperature range. It is concluded that the phase transition between ferroelectric phases of PZN is the one between the tetragonal and rhombohedral phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Here, the piezoelectric response, important in practical applications, becomes enhanced near the morphotropic phase boundary (MPB), which extends parallel to the temperature axis. [12][13][14][15][16][17][18][19][20][21][22][23] By understanding phase diagrams, valuable guidelines for material design can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the piezoelectric response, important in practical applications, becomes enhanced near the morphotropic phase boundary (MPB), which extends parallel to the temperature axis. [12][13][14][15][16][17][18][19][20][21][22][23] By understanding phase diagrams, valuable guidelines for material design can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In the case of relaxor Pb(Zn 1/3 Nb 2/3 )O 3 -ferroelectric PbTiO 3 with a mixing ratio of 1−x:x (PZN-100xPT), an MPB exists between the ferroelectric rhombohedral (R: R3m) phase in the Ti-poor region and the ferroelectric tetragonal (T:P4mm) phase in the Ti-rich region at x ≈ 0.09. 1,2,4) It is widely recognized that monoclinic phases appear near the MPB as a bridge to connect the R and T phases. Around the MPB, the energy states of every phase compete with each other, and relaxor-ferroelectric solid solution single crystals become unstable with respect to the external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…7) Another example is that a ferroelectric phase changes depending on the pretreatment (electric field and temperature history) of the sample. 4,[8][9][10][11] To avoid the complicated situation caused by ferroelectric phases near an MPB, it is beneficial to compare structural features with different compositions in the paraelectric phase. [12][13][14][15][16][17] In the paraelectric phase, precursor phenomena of the phase transition, such as softening of certain ionic vibrations and freezing of dipole relaxation, are observed at the Γ-point of the Brillouin zone and become more pronounced toward the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the tetragonal and rhombohedral phases coexist around the ferroelectric phase transition point in the nonpoled PZN and Pb(In 1=2 Nb 1=2 )O 3 (PIN) crystals on the basis of our experimental results of the dielectric constant measurements. [19][20][21][22] Yokota et al reported that PZT ceramics in the rhombohedral range always consist of mixed phases, on the basis of the experimental results of X-ray diffraction analysis. 23) Asada and Koyama found the aggregation-type ferroelectric domains with an average size of about 10 nm near the MPB in PZT by a transmission electron microscope (TEM) observation.…”
Section: Introductionmentioning
confidence: 99%